Pengaruh Bentuk Tes Terhadap Kemampuan Kognitif Siswa Kelas XI IPA SMAN 4 Banjarmasin Pada Pokok Bahasan Usaha dan Energi - Yunita Arianie; Mustika Wati; Sri Hartini (Berkala Ilmiah Pendidikan Fisika, 2015)
Test form that is given to students allegedly related to cognitive ability. Therefore, conducted aimed research at investigating the effect on cognitive abilities test form students of class XI science SMAN 4 Banjarmasin in subject work and energy. The specific objective of this study are to describe (1) the cognitive abilities of students in the experimental class I drilled essays, (2) cognitive abilities of students in the experimental class II drilled multiple choice, (3) find out whether or not the influence of the use of the test form essay and multiple choice on students cognitive abilities. The study population was all students totaling 104 students with a sample of 57 students. Techniques of data collection through interviews and achievement test. This type of research using quasi-experimental study with the method of analysis used includes validity testing, reliability testing, difficulty level testing, different power testing, requirements analysis testing and ANOVA test (F-test). The results of research that: (1) the cognitive abilities of students in the experimental class I drilled essay mean 60.5912, (2) the cognitive abilities of students in the experimental class II drilled multiple choice means 62.6696, (3) there is the effect of using the form of essays and multiple choice tests to students cognitive abilities. Fratio = 4.6999 > F1:112 = 3.93. Be concluded that there is the effect of the test form to cognitive abilities students.